The correlation between maternal education level and dental caries status among primary school students in West Jakarta: An observational study - Panjaitan, Caesary Cloudya; Lestari, Sri; Oktiviani, Dwi (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2026)
ABSTRACTIntroduction: Oral health remains a public health concern in Indonesia, with dental caries being the most prevalent condition. The 2018 Basic Health Research (Riskesdas) reported high caries prevalence among school-aged children, reaching 92.6% in children aged 5–9 years and 73.4% in those aged 10–14 years. The role of parents, particularly mothers, is crucial in shaping children’s oral hygiene habits. Maternal education level may influence oral health knowledge and practices, as mothers with higher education levels generally provide better care for their children’s teeth. Objective: To analyze the correlation between maternal education level and dental caries status among 4th–6th grade students at SDN Tomang 01, West Jakarta. Methods: This analytical observational study employed a cross-sectional design involving 123 students. Data on maternal education level were collected via questionnaires, and children’s dental caries status was assessed using the DMF-T and def-t indices. Spearman’s correlation analysis was performed using SPSS v30. Results: Spearman correlation analysis revealed a significant negative correlation between maternal education level and children’s dental caries status (p < 0.05). The strength of the correlation ranged from moderate to weak, with the DMF-T index showing a moderate negative correlation (r = –0.449) and the def-t index showing a weak negative correlation (r = –0.258). Conclusion: There is a significant negative correlation, ranging from moderate to weak, between maternal education level and dental caries status in school-aged children. Higher maternal education levels are associated with lower dental caries in children.KEY WORDS: dental caries, DMF-T and def-t, primary school students, maternal education levelKorelasi tingkat pendidikan ibu dengan status karies gigi siswa sekolah dasar: Studi observasionalABSTRAKPendahuluan: Kesehatan gigi dan mulut masih menjadi masalah kesehatan masyarakat di Indonesia, dengan karies gigi sebagai penyakit yang paling banyak ditemui. Hasil Riskesdas 2018 menunjukkan prevalensi karies gigi pada anak sekolah lebih tinggi, yaitu 92,6% pada usia 5–9 tahun dan 73,4% pada usia 10–14 tahun. Kondisi ini dapat dipengaruhi oleh peran orang tua terutama ibu dalam membentuk kebiasaan pemeliharaan kesehatan gigi anak. Tingkat pendidikan ibu dapat mempengaruhi peningkatan pemahaman dan praktik kesehatan, sehingga ibu dengan tingkat pendidikan yang lebih baik umumnya lebih mampu menjaga kesehatan gigi dan mulut anak. Tujuan untuk menganalisis korelasi tingkat pendidikan ibu dengan status karies gigi siswa kelas 4–6 SDN Tomang 01 Jakarta Barat. Metode: Penelitian observasional analitik dengan rancangan cross sectional dengan sampel sebanyak 123 siswa. Pengumpulan data dilakukan dengan menggunakan formulir tingkat pendidikan ibu dan pemeriksaan status karies gigi (DMF-T dan def-t) siswa. Dilakukan uji korelasi Spearman menggunakan SPSS v30 untuk melihat korelasi kedua variabel. Hasil: Analisis korelasi Spearman menunjukkan korelasi negatif yang signifikan antara tingkat pendidikan ibu dengan status karies gigi siswa (p < 0,05). Nilai koefisien korelasi yang dihasilkan berada dalam rentang dari kekuatan sedang hingga lemah, dimana indeks DMF-T menunjukkan korelasi negatif dengan kekuatan sedang (r = –0,449) dan indeks def-t menunjukkan korelasi negatif yang lemah (r = –0,258). Simpulan: Tedapat korelasi negatif dengan kekuatan sedang hingga lemah antara tingkat pendidikan ibu dengan status karies gigi siswa, semakin tinggi tingkat pendidikan ibu maka semakin rendah status karies gigi anak.KATA KUNCI: status karies, DMF-T dan def-t, siswa sekolah dasar, tingkat pendidikan